Analysis Of Application Of Psak No. 34 (2015 Adjustment) Above Recognition Of Income And Expenses Pt Duta Borneo Madani - Yogi Arif Prabowo (Indonesian Journal of Business, Accounting and Management (IJBAM), 2018)
Abstract—The study aims to determine the recognition of revenues and expenses at one of the growing construction companies in Indonesia named PT Duta Borneo Madani accordance with standar principles of Statement of Financial Accounting Standards or PSAK No. 34 with an adjustment in 2015. The research model uses Percentage of Completion Method Kieso, Weygandt, and Warfield with the cost method (Cost to cost). This study uses primary data obtained from the collection of interviews of respondents as many as three people as accounting and finance practitioners, and policy makers who influence the progress of the increase in revenues and expenses in the corporate environment.In addition, secondary data were also obtained interpretation of data from the primary data of previous studies, books, or reference support obtained from the journal. The data analysis in this research use descriptive qualitative data analysis techniques model of Miles & Huberman. A summary of this study, the first, the results of revenue and expenses recognized companies differ significantly from the methods that result from PSAK No. 34 (Adjustment 2015), it affects the different profit. Second, there are differences in the journal entries of revenues and expenses, as well as the effect on revenues and expenses where the completed contract method of revenue and expenses do not reflect the real situation, in contrast to the percentage